Unravelling the GSK3β-related genotypic interaction network influencing hippocampal volume in recurrent major depressive disorder. (October 2018) - Inkster, Becky; Simmons, Andy; Cole, James H.; Schoof, Erwin; Linding, Rune; Nichols, Tom; Muglia, Pierandrea; Holsboer, Florian; Sämann, Philipp G.; McGuffin, Peter; Fu, Cynthia H.Y.; Miskowiak, Kamilla; et al.
Abstract : Objective: Glycogen synthase kinase 3β (GSK3β) has been implicated in mood disorders. We previously reported associations between a GSK3β polymorphism and hippocampal volume in major depressive disorder (MDD). We then reported similar associations for a subset of GSK3β-regulated genes. We now investigate an algorithm-derived comprehensive list of genes encoding proteins that directly interact with GSK3β to identify a genotypic network influencing hippocampal volume in MDD. Participants and methods: We used discovery ( N =141) and replication ( N =77) recurrent MDD samples. Our gene list was generated from the NetworKIN database. Hippocampal measures were derived using an optimized Freesurfer protocol. We identified interacting single nucleotide polymorphisms using the machine learning algorithm Random Forest and verified interactions using likelihood ratio tests between nested linear regression models. Results: The discovery sample showed multiple two-single nucleotide polymorphism interactions with hippocampal volume. The replication sample showed a replicable interaction (likelihood ratio test: P =0.0088, replication sample; P =0.017, discovery sample; Stouffer's combined P =0.0007) between genes associated previously with endoplasmic reticulum stress, calcium regulation and histone modifications. Conclusion: Our results provide genetic evidence supporting associations between hippocampal volume and MDD, which may reflect underlying cellular stress responses. Our study provides evidence of biological mechanisms that should be further explored in the search for disease-modifying therapeutic targets for depression. Abstract : Supplemental Digital Content is available in the text.